The power of words : studies on charms and charming in Europe - Kapaló, James Alexander (Central European University Press, 2013)
In medieval and early modern Europe, the use of charms was a living practice in all strata of society. The essays in this book explore the rich textual tradition of archives, monasteries, and literary sources. The book also discusses texts amassed in folklore archives and ones that are still accessible through field work in many rural areas of Europe.